Building on Bion-- branches : contemporary developments and applications of Bion's contributions to theory and practice - Lipgar, Robert M., 1928-2018; Pines, Malcolm (International library of group analysis, 2003)
The enduring influence of Bion's work - the many rich applications of his ideas to group therapy, group dynamics and organisational dynamics in the present day and looking to the future - is the central theme of this book. Chapters by distinguished international contributors from the fields of psychoanalysis, group analysis, management consultancy and social science cover work with large groups, Bion and the Tavistock conferences, and his ideas about thinking and learning, dreams and mentality. They clearly demonstrate Bion's originality and passion as he sought the distinctive essence of psyc.